BUILDING SUSTAINABILITY AWARENESS: INTEGRATING ESD INTO HUMAN DIGESTIVE SYSTEM EDUCATION - Setiani, Rina; M. Syaipul Hayat; Roshayanti, Fenny; Sumarno (BIOMA : Jurnal Ilmiah Biologi, 2025)
In response to global environmental challenges such as climate change, pollution, and resource depletion, this study aimed to develop and evaluate Education for Sustainable Development (ESD)–oriented science learning materials on the human digestive system to enhance students’ sustainability awareness. Employing a Research and Development (R&D) approach and the ADDIE model, the instructional materials were implemented in a quasi‑experimental design with two eighth‑grade groups at SMP Negeri 2 Tulis during the 2024/2025 odd semester. Sustainability awareness was measured using a 26‑item questionnaire administered as a pretest and posttest. The experimental group, which received the ESD‑oriented intervention, demonstrated a mean pretest score of 70.55 and a posttest score of 92.06 (mean N‑Gain = 0.63). The experimental group showed significantly higher gains in both sustainability awareness—especially in emotional engagement—compared to the control group. These outcomes suggest that integrating ESD into science learning not only improves conceptual understanding but also shaping environmentally responsible and reflective students.